Review of Lipid Synthesis in Cow’s Milk - Rahimi, Manizha (Journal of Natural Sciences – Kabul University, 2021)
Lipids are major biological molecules and serve as an essential form of energy storage in animals. Lipids can be categorized into three groups: simple lipids, complex lipids, and phospholipids. The most common form of lipids is triglycerides. The lactating mammary gland is one of the most active triglyceride-synthesizing organs in the body. Triglycerides are major constituents of the milk of most mammals, providing a significant portion of the calories required for neonatal growth and a source of essential fatty acids. Milk lipids are secreted as cytoplasmic assemblies of triglyceride droplets surrounded by a phospholipid monolayer and surface-associated proteins called cytoplasmic lipid droplets (CLDs). CLDs are generated at the endoplasmic reticulum through a mechanism that is not fully understood. Adipophilin, a lipid droplet-associated protein, promotes CLD accumulation by inhibiting triglyceride lipolysis. Adipophilin is abundantly found in the mammary gland, and its size is closely related to the accumulation of CLDs.